Novel IRF6 mutations in families with Van Der Woude syndrome and popliteal pterygium syndrome from sub-Saharan Africa. - Butali, Azeez; Mossey, Peter A; Adeyemo, Wasiu L; Eshete, Mekonen A; Gaines, LauRen A; Even, Dee; Braimah, Ramat O; Aregbesola, Babatunde S; Rigdon, Jennifer V; Emeka, Christian I; James, Olutayo; Ogunlewe, Mobolanle O; et al. (Molecular Genetics and Genomic Medicine, 2024)
7p